Investigation of support effect on CO adsorption and CO + O2 reaction over Ce1 − x − yMxCuyO2 − δ (M = Zr, Hf and Th) catalysts by in situ DRIFTS. (3rd July 2015) - Baidya, Tinku; Bera, Parthasarathi
Abstract : Adsorption of CO as well as CO+O2 reaction over Cu 2+ ion substituted Ce1 − x Mx O2 (M = Zr, Hf and Th) supports have been studied by DRIFTS. Linear Cu + –CO bands are observed over all catalysts upon introduction of CO. But, Cu + –CO band positions are shifted to little higher frequencies in Ce0.68 M0.25 Cu0.07 O2 − δ compared to Ce0.93 Cu0.07 O2 − δ . However, Cu + –CO bands are in same positions when CO and O2 are adsorbed simultaneously over all the catalysts. Ramping the temperature in the DRIFTS cell after simultaneous CO and O2 adsorption shows the formation of CO2 as well as decrease of CO. Comparison of intensities of CO2 bands of different catalysts as a function of temperature indicates that Ce0.68 Th0.25 Cu0.07 O2 − δ shows lowest temperature CO oxidation among all the catalysts that is because of its more electron withdrawing power. Graphical Abstract: